Gender Equality in Educational Management in Educational Institutions - Evi Muafia; Wilis Werdiningsih (Didaktika Religia, 2021)
Gender equality in educational institutions is something that must be realized. Gender equality examines efforts to equalize the two sexes so that both can benefit equally in life. One of the efforts that can be done is to implement education management in educational institutions. This study aims to examine the implementation of education management in educational institutions in realizing gender equality. The library research method is used by extracting information from various literature related to gender equality and education management and its implementation in educational institutions. The results show that the performance of education management to realize gender equality can be carried out through HR management activities and student management. In HR management, efforts to achieve gender equality can be carried out by ensuring the proportional involvement of male and female school members in all school activities. The indicators of gender equality, namely access, participation, control, and benefits, show this phenomenon. The next effort is to carry out gender-responsive learning activities.